2012
DOI: 10.3109/17549507.2012.713394
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia training for speech-language pathologists: Implications for clinical practice

Abstract: There are competency standards available in countries with established speech-language pathology services to guide basic dysphagia training with ongoing workplace mentoring for advanced skills development. Such training processes however are not as well established in countries where speech-language pathology training and practice is relatively new such as Malaysia. The current study examines the extent of dysphagia training and workplace support available to speech-language pathologists (SLPs) in Malaysia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Recent research has confirmed that Malaysian clinicians currently have poor computer access, unreliable internet reception and lack of access to online journals or internet web browsing (Mustaffa Kamal et al 2012;Sharma et al 2010). Hence the professional development model developed for the current context consisted of 16 hours of dysphagia education delivered in four, face to face 4-hour workshops run once per week over four consecutive weekends.…”
Section: Dysphagia Workhopsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent research has confirmed that Malaysian clinicians currently have poor computer access, unreliable internet reception and lack of access to online journals or internet web browsing (Mustaffa Kamal et al 2012;Sharma et al 2010). Hence the professional development model developed for the current context consisted of 16 hours of dysphagia education delivered in four, face to face 4-hour workshops run once per week over four consecutive weekends.…”
Section: Dysphagia Workhopsmentioning
confidence: 99%
“…In light of recent findings which have reported that Malaysian SLPs had reduced levels of knowledge, skills and confidence in managing dysphagia largely due to minimal training and clinical support opportunities (Mustaffa Kamal et al 2012;Sharma et al 2006), the current study aimed to address these training needs in order to help facilitate the development of dysphagia services in Malaysia. In particular, the current study is an evaluation of a professional development model that incorporates various methods into teaching theoretical and practical application of knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations